Perancangan Sistem Informasi Pemesanan Tiket Bus Berbasis Web Pada PO. Aurel Jambi - Muhammad Fajar; Eni Rohaini; mery (LPPM Universitas Dinamika Bangsa, 2023)
PO.Aurel is a company that offers transportation services in which the process of ordering tickets is still done manually by calling by phone or WhatsApp so that customers have limited information or come directly to the Aurel bus counter to get more detailed information about ordering. Data processing and report preparation are still carried out with the help of books so that sometimes errors can occur in recording which cause data inaccuracies. For the process or promotion of information dissemination only via the telephone number listed at the bus counter location, this method is less effective and efficient. Therefore, the purpose of this research is to analyze the system that is currently running in order to overcome the problems faced at PO.Aurel by designing a Web-Based Bus Ticket Booking Information System at PO.Aurel. The system development method uses the waterfall model, this implementation research uses the PHP Programming Language and Laravel Framework version 6 and MySQL DBMS, to produce applications that can make it easy for customers to place orders and PO.Aurel in processing data orders with both from searching, calculating, ordering, paying, making reports needed so that it is better and systemized.